Pengaruh Nilai-Nilai Budaya Batak Terhadap Pelayanan Publik Di Desa Parmonangan Kecamatan Pakkat - Gajah, Nurhamidah; Arifana, Arifana; Gajah, Rahmadi (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2024)
The purpose of this study was to determine how the implementation of the value of Batak culture values in the Parmonangan Village office, then to find out how Public Services at the Parmonangan Village Office and to find out how much influence the value of Batak cultural values has on public services at the Parmonangan Village office.The research method used is a type of quantitative research by taking respondents from the Parmonangan Village community as many as 76 people.The results showed that the Batak Cultural values of Kinship, Hasangapon, Hamajuon and Hamoraon are highly upheld and applied by the community including in the Parmonangan Village office. Public Services at the Parmonangan Village office fall into the Moderate category, meaning that service procedures, completion time, equality of treatment and openness are sometimes implemented and sometimes not implemented. So it can be concluded that both variables can be said to be valid because r count (0.2172) r table (0.1901). From the results of hypothesis testing, it can be seen that tcount = 16.7425 and the ttable is 1.993, so tcount than ttable (16.7425 1.993) so that the hypothesis can be accepted. Based on the results of the determination test, the effect of Batak cultural values on public services is 5%.